Volume of nerve fibers in the stress-induced bladder of adult rats following capsaicin treatment - ERCAN, FERİHA (KARGER, 2003)
Introduction: We have investigated the volume of nerve fibers in the rat urinary bladder following systematic exposure to cold-restraint stress and capsaicin treatment. Materials and Methods: Adult Wistar albino rats were either exposed to cold-restraint stress (vehicle group) or treated with capsaicin before exposure to cold-restraint stress (capsaicin group). In the control group, animals were neither exposed to cold-restraint stress nor given capsaicin. From each group, samples of bladder were prepared for morphological investigation and stereological evaluation of the volume of nerve fibers. Results: Stress exposure was associated with urothelial degeneration, a higher incidence and degranulation of mast cell profiles in the mucosa, and an increased volume of nerve fibers in the muscular layer of the bladder wall. Capsaicin treatment prevented the stress-induced degenerative changes. In the capsaicin group, the volume of nerve fibers in the muscular layer was also significantly smaller than that in the stress group. Conclusions: Exposure of adult rats to capsaicin prevented the stress-induced degeneration of the bladder and changed the volume of capsaicin-sensitive fibers in muscular layer. We conclude that capsaicin and related compounds may be useful in treating stress-induced bladder problems. Copyright (C) 2003 S. Karger AG, Basel.
Keywords: capsaicin; stress-induced bladder; stereological evaluation; interstitial cystitis; INTERSTITIAL CYSTITIS; SUBSTANCE-P; AFFERENT NEURONS; URINARY-BLADDER; SYSTEM